Ethnomedicinal Plants Used for Treatment of Infectious Diseases by Dayak Ethnic in Borneo, Indonesia - Nawan, Nawan; Handayani, Septi; Toemon, Agnes Immanuela (Global Medical & Health Communication (GMHC), 2024)
The Dayak tribe, residing on the island of Borneo in Indonesia, continues to uphold their ancestral cultural customs involving using medicinal plants for disease treatment. To assess the efficacy of chosen Dayak traditional medicinal plants, commonly utilized for treating diverse infectious ailments, against bacteria responsible for infections. Samples of medicinal plants (Garptophyllum pictum, Eleutherine bulbosa, Oscimum sanctum, Cassia alata, Callicarpa longifolia Lam., Hibiscus rosa-sinensis, Dracaena cantleyi, Uncaria gambir Roxb., Rhodomyrtus tomentosa, Gomphrena globose) were extracted using absolute methanol and water and tested for their antimicrobial activities against stock isolates and standard strains of Staphylococcus aureus, Streptococcus pyogenes, Escherichia coli, Pseudomonas aeruginosa, Enterobacter aerogenes using agar well diffusion and micro titer plate methods. Crude extracts of Eleutherine bulbosa, Dracaena cantleyi, Oscimum sanctum, and Uncaria gambir Roxb. inhibited bacterial growth by 100%, 100%, 40%, and 25% against the test organisms, respectively. These plants inhibited the growth of bacteria from 7 mm to 16 mm in diameter. Most of the plant extracts had antibacterial activities, among which Eleutherine bulbosa and Dracaena cantleyi inhibited the growth of 100% of the test organisms, respectively. The activities of methanolic extracts were greater than those of their corresponding water extracts. Streptococcus pyogens was the organism most susceptible to the extract, while Enterobacter aerogenes demonstrated the highest resistance.